Paediatric tele-emergency care: A study of two delivery models. (January 2021) - Weigel, Paula A; Merchant, Kimberly AS; Wittrock, Amy; Kissee, Jamie; Ullrich, Fred; Bell, Amanda L; Marcin, James P; Ward, Marcia M
Introduction: Tele-emergency models have been utilized for decades, with growing evidence of their effectiveness. Due to the variety of tele-emergency department (tele-ED) models used in practice, however, it is challenging to build standardized metrics for ongoing evaluation. This study describes two tele-ED programs, one specialized and one general, that provide care to paediatric populations. Through an examination of model structures and patient populations, we gain insight into how evaluative measures should reflect tele-ED model design and purpose. Methods: Qualitative descriptions of the two tele-ED models are presented. We show a retrospective cohort analysis describing paediatric patients' key characteristics, reasons for visit, and disposition status by case/control status. Case/control patient encounter data were collected October 2015 through December 2017, from 15 spoke hospitals within each tele-ED program. Results: The two tele-ED models serve distinct paediatric populations, and measures of tele-ED utilization and disposition reflect those differences. In the specialized University of California (UC) Davis Health program, tele-ED was utilized in 36% of paediatric critical care encounters and 78% of those were transferred. In the Avera eCARE program, tele-ED was activated in 1.7% of paediatric encounters and 50.6% of those were transferred. When Avera eCARE paediatric encounters were stratified by severity, measures of tele-ED use and disposition status among high-severity encounters were more similar to UC Davis Health. Discussion: This study describes how design choices of tele-ED models have implications for evaluative measures. Measures of tele-ED model success need to reflect model purpose, populations served, and for whom tele-ED service use is appropriate.